Technetium-99m chelator-free radiolabeling of specific glutamine tumor imaging nanoprobe: in vitro and in vivo evaluations - Ghoreishi, Seyedeh Masoumeh (Int J Nanomedicine, 2018)
INTRODUCTION: Nowadays, molecular imaging radiopharmaceuticals’, nanoparticles’, and/or small-molecule biomarkers’ applications are increasing rapidly worldwide. Thus, researchers focus on providing the novel, safe, and cost-effective ones. MATERIALS AND METHODS: In the present experiment, technetium-99m ((99m)Tc)-labeled PEG-citrate dendrimer-G(2) conjugated with glutamine (nanoconjugate) was designed and assessed as a novel tumor imaging probe both in vitro and in vivo. Nanoconjugate was synthesized and the synthesis was confirmed by Fourier transform infrared, proton nuclear magnetic resonance, liquid chromatography-mass spectrometry, dynamic light scattering, and static light scattering techniques. The toxicity was assessed by XTT and apoptosis and necrosis methods. RESULTS: Radiochemical purity indicates that the anionic dendrimer has a very high potential to complex formation with (99m)Tc and is also very stable in the human serum in different times. Results from the imaging procedures showed potential ability of nanoconjugates to detect tumor site. CONCLUSION: Suitable features of the anionic dendrimer show that it is a promising agent to improve nanoradiopharmaceuticals.